Effect of the Savi (Somatic, Audio, Visual, Intellectual) Learning Model on Fifth Grade Science Learning Outcomes at SD Negeri 124398 Pematangsiantar - Ezion Gus Frenanda Saragih; Janwar Tambunan; Rio Parsaoran Napitupulu (International Journal of Technology and Education Research, 2026)
This study is based on the observation of researchers in grade V of UPTD SD Negeri 124398 Pematangsiantar that teachers still use conventional learning models so that students are less involved in the learning process. This causes the learning process to be less than optimal and student learning outcomes do not meet the criteria for achieving learning objectives. From these problems, it is necessary to find solutions, including by implementing the SAVI (Somatic, Audio, Visual, Intellectual) learning model. This learning model can be applied to science subjects because it encourages students to work together and communicate with each other in completing their tasks. This learning model can improve the quality of science learning so that students are more active, creative, and innovative so that learning outcomes improve. This study uses a quantitative method with a Pre-Experiment research type and a One Group Pretest-Posttest research design with a sample of 22 students. Based on the results of the hypothesis test with a significance level of 0.05, the calculated t is 24.159, with a significance level (2-tailed) of 0.000, a probability of significance <0.05, and a calculated t table of 24.159 > 1.717, Ho is rejected and H1 is accepted. This explanation indicates that the SAVI (Somatic, Audio, Visual, Intellectual) learning model has an effect on the science learning outcomes of fifth-grade students at the UPTD of SD Negeri 124398 Pematangsiantar.